Inside Back Cover: On‐Surface Synthesis of Ethynylene‐Bridged Anthracene Polymers (Angew. Chem. Int. Ed. 20/2019). Issue 20 (8th April 2019) - Sánchez‐Grande, Ana; de la Torre, Bruno; Santos, José; Cirera, Borja; Lauwaet, Koen; Chutora, Taras; Edalatmanesh, Shayan; Mutombo, Pingo; Rosen, Johanna; Zbořil, Radek; Miranda, Rodolfo; Björk, Jonas; et al.
Abstract : Atomically precise ethynylene‐bridged anthracene polymers have been fabricated on noble‐metal substrates from quinoid precursors endowed with =CBr2  moieties. In their Communication on page 6559 ff., J. Björk, P. Jelínek, N. Martín, D. Écija et al. demonstrate that the deposition of these precursors on Au(111) at room temperature and subsequent annealing above 400 K results in the formation of long and defect‐free one‐dimensional polymers by homocoupling and aromatization.